Methylated HNRNPK acts on RPS19 to regulate ALOX15 synthesis in erythropoiesis - Naarmann-de Vries, Isabel S.; Senatore, Roberta; Moritz, Bodo; Marx, Gernot; Urlaub, Henning; Niessing, Dierk; Ostareck, Dirk H.; Ostareck-Lederer, Antje (Nucleic acids research, 2021)
Post-transcriptional control is essential to safeguard structural and metabolic changes in enucleated reticulocytes during their terminal maturation to functional erythrocytes. The timely synthesis of arachidonate 15-lipoxygenase (ALOX15), which initiates mitochondria degradation at the final stage of reticulocyte maturation is regulated by the multifunctional protein HNRNPK. It constitutes a silencing complex at the ALOX15 mRNA 3 ' untranslated region that inhibits translation initiation at the AUG by impeding the joining of ribosomal 60S subunits to 40S subunits. To elucidate how HNRNPK interferes with 80S ribosome assembly, three independent screens were applied. They consistently demonstrated a differential interaction of HNRNPK with RPS19, which is localized at the head of the 40S subunit and extends into its functional center. During induced erythroid maturation of K562 cells, decreasing arginine dimethylation of HNRNPK is linked to a reduced interaction with RPS19 in vitro and in vivo. Dimethylation of residues R256, R258 and R268 in HNRNPK affects its interaction with RPS19. In noninduced K562 cells, RPS19 depletion results in the induction of ALOX15 synthesis and mitochondria degradation. Interestingly, residue W52 in RPS19, which is frequently mutated in Diamond-Blackfan Anemia (DBA), participates in specific HNRNPK binding and is an integral part of a putative aromatic cage.
Gesehen am 07.07.2021